2021
DOI: 10.3390/molecules26195741
|View full text |Cite
|
Sign up to set email alerts
|

Bile-Acid-Appended Triazolyl Aryl Ketones: Design, Synthesis, In Vitro Anticancer Activity and Pharmacokinetics in Rats

Abstract: A library of bile-acid-appended triazolyl aryl ketones was synthesized and characterized by detailed spectroscopic techniques such as 1H and 13C NMR, HRMS and HPLC. All the synthesized conjugates were evaluated for their cytotoxicity at 10 µM against MCF-7 (human breast adenocarcinoma) and 4T1 (mouse mammary carcinoma) cells. In vitro cytotoxicity studies on the synthesized conjugates against MCF-7 and 4T1 cells indicated one of the conjugate 6cf to be most active against both cancer cell lines, with IC50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Thirdly Agarwal et al [16], illustrated that Bile acid appended triazoyl aryl ketones 6af as well as 6cf resulted in apoptosis induction in MCF7 cells breast cancer cells (Figure 3D). Specifically substance 6cf led to apoptosis induction by 46.09% in MCF7 cells whereas substance 6af led to apoptosis induction by 33.89%, illustrating that 6cf possesses greater effectiveness regarding apoptosis induction.…”
Section: Cell Death Modes Of Synthetic Bile Acids Prototypical Agents...mentioning
confidence: 87%
See 1 more Smart Citation
“…Thirdly Agarwal et al [16], illustrated that Bile acid appended triazoyl aryl ketones 6af as well as 6cf resulted in apoptosis induction in MCF7 cells breast cancer cells (Figure 3D). Specifically substance 6cf led to apoptosis induction by 46.09% in MCF7 cells whereas substance 6af led to apoptosis induction by 33.89%, illustrating that 6cf possesses greater effectiveness regarding apoptosis induction.…”
Section: Cell Death Modes Of Synthetic Bile Acids Prototypical Agents...mentioning
confidence: 87%
“…Additionally, various laboratories have generated innovative Bile Acid obtained substance for evaluation of the tumor suppressive actions of bile acids. These substances were illustrated to result in induction of programmed cell death (PCD) in different cancer cells besides possess tumor repressive action [14][15][16][17][18][19][20][21][22][23][24]. Cell death possesses a key part in embryonic formation, sustenance of homeostasis, as well as elimination of injured cells.…”
Section: Introductionmentioning
confidence: 99%
“…Third, Agarwal et al [24] showed that the bile acid-added triazolyl aryl ketones 6af and 6cf induced apoptosis in MCF-7 breast carcinoma cells (Figure 3D). In particular, compound 6cf induced apoptosis by 46.09% in MCF-7 cells, and compound 6af induced apoptosis by 33.89%, showing that 6cf was more effective in inducing apoptosis.…”
Section: Cell Death Mechanism Of Synthetic Bile Acid Derivatives In C...mentioning
confidence: 93%
“…In addition, several laboratories have synthesized novel bile acid derivatives to explore the tumor-suppressive function of bile acids. These derivatives were shown to induce programmed cell death in several cancer cells, and have tumor-suppressive effects [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from optical density values were utilised to calculate the percentage cell viability. The samples were also analysed for microscopic observation using an optical microscope 35 .…”
Section: Methodsmentioning
confidence: 99%